NILAI PENDIDIKAN KARAKTER SISWA DALAM PEMBIASAAN SHADAQAH SENTRA BALAI REHABILITASI SOSIAL MARSUDI PUTRA ANTASENA SALAMAN KABUPATEN MAGELANG - Fatchurrahman Fatchurrahman; Umi Sa’adatul Maulidiyah (Universitas Islam Madura, 2023)
The rampant moral crisis of beneficiary children at the Marsudi Putra Antasena Salaman Magelang Social Rehabilitation Center is caused by several factors for beneficiary children by returning deviations from the moral crisis through the habit of giving alms and religious coaching. This research method uses a qualitative approach with the concept of naturalistic inquiry which seeks to reveal the reality of the phenomenon of the value of student character education in the habituation of sadaqah by using data from texts, interviews, observations and documentation to provide clarity on the situation or reality. The results of this study indicate that the implementation is carried out through the habit of giving alms by giving motivation, giving understanding, giving advice, while in the implementation process giving good examples for beneficiaries, giving awards to beneficiary children, and providing skill activities for beneficiary children. The value of character education that is formed through the habituation of alms can bring up religious character, discipline, social care, and responsibility. The problems are self-awareness of beneficiary children, family disharmony, growing technological advances, lots of free time, and lack of parental monitoring. The implication of this research is that the formation of character in the form of the habit of caring for one another, such as liking to give charity, can be realized in today's teenagers and young people.